Aplikasi Pencarian Informasi Al-Quran dengan Ontologi Web Semantik - Safira, Safira; Santiyasa, I Wayan; Wibawa, I Gede Arta; ER, Ngurah Agus Sanjaya; Dwidasmara, Ida Bagus Gede; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2022)
Al-Quran is the holy book of Muslims which consists of 30 chapters, 114 surahs, and 6236 verses. Each juz in the Quran can contain one or more surah and each surah consists of a different number of verses. Seeing the many contents of the knowledge of the Quran, then this can help someone to find and determine the theme of the surah to be read manually. In this study, the authors build a system that is expected to facilitate one's work in searching for the contents of the Al-Quran by using ontology as the backbone of the system, Methonology as a method for building an ontology model, and Prototyping as a system development method.